Unique product quality considerations in vaccine development, registration and new program implementation in Malaysia. Issue 3 (3rd March 2020) - Khoo, Yvonne S. K.; Ghani, A. Ab; Navamukundan, A. A.; Jahis, R.; Gamil, A.
ABSTRACT: This review aims to present the unique considerations for manufacturing and the regulation of new vaccines in Muslim-populated countries such as Malaysia. Our specific objectives are to highlight vaccine production and the ingredients of concern, summarize the current mechanism for ruling and recommendations on new vaccines, outline the different steps in decision-making on incorporating a new vaccine into the National Immunization Program, describe its issues and challenges, and explore the commercial viability and challenges of producing local permissible ( halal) vaccines. Through this review, we hope readers understand that alternatives are present to replace ingredients of concern in vaccines. Halal certification and introduction of a new vaccine into a program are strictly conducted and health-care providers must be prepared to educate the public on this. At the same time, it is hoped that the production of halal vaccine in Malaysia will promote self-reliance in Muslim-populated countries.